Structuring Complex or Wicked Problems: A Multimethod Approach in Practice - Hernandez, Alejandro (European conference on research methodology for business and management studies, 2023)
Complex or wicked problems necessarily require multidisciplinary approaches to shape the issue(s) into a structure that can lead to viable solutions. This paper presents a case in which a systematic approach was used to combine structuring methods to support a research design that intended to quantitatively relate variables which have been insufficiently defined. Misconstrued definitions of variables and the dearth or missing data are just some of the characteristics that make this problem “complex.” The scientist’s primary work in the early stages of this type of research effort is to apply a series of techniques that meaningfully define the variables, specify relevant data to support development of quantitative models, and generate and\or collect that data. The sequence of discussion in this paper is a multimethod outline for addressing complex problems. This paper begins by defining complex or wicked problems. Next, an illustrative military problem that exhibits complex characteristics is presented. Sequentially, various structuring techniques from several fields of study such as systems engineering, operations research, and computer science are discussed and applied to the problem. Activities began with a workshop to learn about the problem and provide context. This venue allowed primary stakeholders to describe the variables from their stance. During the workshop, participants conceptualized relationships among the variables. An in-depth literature review before and after the workshop informed development of theories and hypotheses about the variables and plausible connections among them. Using functional decomposition, the team broke down the variables into their fundamental components. Relational matrices and causal loop diagrams formed initial ideas for how the components may be linked. Functional decomposition syntax also led to relevant, quantifiable measures that afforded an opportunity to mathematically formulate relationships among components, thereby achieving the primary objective of the problem. Blending techniques from different disciplines and their respective structuring methods is a powerful approach for creating conditions to solve complex or wicked problems. The utility of this study is in identifying the critical properties of a complex or wicked problem and mapping suitable methods to “tame” them. The overall approach is applicable to complex problems found in industry, government, and scientific research.